Impact of Calcium Fructoborate on WOMAC and McGill Subscales and Individual WOMAC Questions: Post-Hoc Analyses of Data from a Previously Published 90-Day Randomized Clinical Trial - Robinson, Jennifer; Nemzer, Boris; Reyes-Izquierdo, Tania; Pietrzkowski, Zbigniew; Hunter, John M (European Journal of Applied Sciences, 2023)
Calcium fructoborate (CFB) has been shown to reduce overall joint discomfort on the Western Ontario and McMaster University Arthritis Index (WOMAC) and the McGill Pain Questionnaire (MPQ). No study has addressed the impact of CFB on the subscales of these measures, nor on individual questions. Here, we re-examined data from a previously peer reviewed and published 90-day, double-blind, randomized, placebo-controlled study on CFB to determine whether there were subscale or individual questions differences. In the original study participants were randomized into three groups: 1) placebo, 2) a morning dose of 216mg of CFB and evening dose of placebo (CFB1), or 3) a morning and evening dose of 108mg of CFB (CFB2). Our new analyses indicated that by day 30, both CFB groups were distinguishable from placebo on the WOMAC Pain and WOMAC Activities of Daily Living subscales. Furthermore, they were distinguishable from the WOMAC Stiffness subscale by days 60 and 90 (CFB1, CFB2, respectively). Importantly, analyses of individual WOMAC questions revealed differences in at little as 14 days. For the McGill pain subscale, differences emerged by day 7 and 14 between placebo and CFB1/CFB2 groups, respectively, while the affective dimension was different from CFB groups by day 60. For the miscellaneous dimension, placebo was differentiable by day 60 and 90 (CFB1/CFB2, respectively). These data provide greater visibility into CFB’s joint health benefits and suggest that CFB’s effects support real improvements in practical aspects of daily physical activity.